Theodor Arldt (1878–1960): Parochial Pauker and Pioneering Palaeobiogeographer - Ebach, Malte C.; Dowding, Elizabeth M. (Zootaxa, 2017)
The rise and fall of Theodor Karl Hermann Arldt (1878–1960) took place in Radeberg, a small town in Saxony between 1902 and 1945, where he supported his research by working as a school headmaster or Pauker. Within his many scientific papers and books Arldt pioneered palaeogeography and palaeobiogeography by introducing distributional data of living organisms to understand past continental connections. His writings influenced notable scientists such as Alfred Wegener and partially influenced the geological community in which palaeogeography was firmly rooted. While Arldt’s biogeographic approach was novel, and in hindsight surprisingly modern, it failed to engage biologists where such a method may have flourished. As a small town Pauker, Arldt had little or no contact with universities and university students, leaving a legacy of pioneering publications and ideas but no one to carry them forward into the post-tectonic world of the 1960s.